Respostas
respondido por:
1
2x+y=24 I multiplique a equação I por (-1)
5x+y=60 II
-2x-y= -24
5x+y=60
--------------
3x+0y =36 Agora é só substituir x em quaisquer das equações:
3x=36 2x+y=24
x=36/3 2*12+y=24
x=12 24+y=24
y=24-24
y=0
5x+y=60 II
-2x-y= -24
5x+y=60
--------------
3x+0y =36 Agora é só substituir x em quaisquer das equações:
3x=36 2x+y=24
x=36/3 2*12+y=24
x=12 24+y=24
y=24-24
y=0
respondido por:
1
{2x+y=24 (-1)
{5x+y=60
{-2x-y=-24
{5x+y=60
3x=36
x=36/3
x=12
espero ter ajudado (:
{5x+y=60
{-2x-y=-24
{5x+y=60
3x=36
x=36/3
x=12
espero ter ajudado (:
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás